Prediction of the Antiinflammatory Activity of New S-alkyl Derivatives of 1,2,4-triazol-3-thiones Using the PASS Computer Program and Molecular Docking - Natalya Mykolaivna Chalenko; Anna Olegovna Syrovaya; Natalya P Kobzar; Maryna V Rakhimova; Irina A Sych; Igor Vladimirovich Sych (Borneo Journal of Pharmacy, 2020)
The strategy of rational approaches to the search for selective COX-2 inhibitors as potential antiinflammatory agents has been proposed and elaborated. It is based on the use of PASS-prediction and molecular docking. The choice of the basic structure of 4-amino-3-thio-1,2,4-triazole as a promising object of chemical modification has been substantiated. Using a modification of the primary molecule, a virtual library of S-derivatives of 5-substituted 4-amino(pyrrol)3-thio-4H-1,2,4-triazoles in the amount of 100 compounds (ten groups) has been obtained by introducing various pharmacophore fragments. Based on the analysis of the results of the PASS-prediction and molecular docking, six of the ten planned groups of compounds have been selected for the synthesis as promising selective COX-2 inhibitors. The reliability of the prediction results has already been confirmed for one of the promising group 4-amino-5-(pyridine-4-yl)-1,2,4-triazole (4Н)-3-yl-thioacetamides.